The hundred languages of children : the Reggio Emilia approach--advanced reflections - Edwards, Carolyn P.; Gandini, Lella; Forman, George E. (Greenwich, Conn. : Ablex Pub. Corp., 1998)
Leading children to surprising levels of symbolic skill and creativity, the system is not private and elite but rather involves full-day child care open to all, including children with disabilities
Includes bibliographical references and indexes.
Keywords: Early childhood education -- Italy -- Reggio Emilia; Early childhood education -- Case studies. -- United States; Reggio Emilia approach (Early childhood education)